PELATIHAN PEMANFAATAN APLIKASI MENDELEY DESKTOP UNTUK MENGELOLA REFERENSI KARYA ILMIAH MAHASISWA - Widayat, Prabowo Adi; Najib, Khotim Hanifudin (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
References are the most important part of writing good scientific work. There are not a few scientific works that are not supported by relevant references. This is due to the lack of author skills in utilizing good reference management applications. Coupled with the various styles of reference writing, the writer often makes mistakes in writing references according to the appropriate style of the context. This community service activity aims to improve students' skills in utilizing the Mendeley reference management application as a tool for managing references. Service activities are carried out through three stages, namely planning, implementation and evaluation. Mendeley training activities are carried out in a hybrid manner, online and offline. The training participants were final-year students totaling 48 students. The results of the training activities included, first, students could improve their skills in managing references with Mendeley which could assist them in writing their final assignment. Second, there are several obstacles in the implementation of this training such as technical constraints in the form of an internet network, lack of power plugs, incompatible laptops, and limited space. Third, the trainees felt that Mendeley's training would be beneficial for the completion of their final assignment.